Potentially suitable geographical area for Pulsatilla chinensis Regel under current and future climatic scenarios based on the MaxEnt model - Wu, Yanan; Yan, Lanmeng; Shen, Hongjian; Guan, Rui; Ge, Qianqian; Huang, Ling; Rohani, Emelda Rosseleena; Ou, Jinmei; Han, Rongchun; Tong, Xiaohui (Frontiers in Plant Science, 2025)
Climate change has significantly impacted the distribution patterns of medicinal plants, highlighting the need for accurate models to predict future habitat shifts. In this study, the Maximum Entropy model to analyze the habitat distribution of Pulsatilla chinensis (Bunge) Regel under current conditions and two future climate scenarios (SSP245 and SSP585). Based on 105 occurrence records and 12 environmental variables, precipitation of the wettest quarter, isothermality, average November temperature, and the standard deviation of temperature seasonality were identified as key factors influencing the habitat suitability for P. chinensis. The reliability of the model was supported by a mean area under the curve (AUC) value of 0.916 and a True Skill Statistic (TSS) value of 0.608. The results indicated that although the total suitable habitat for P. chinensis expanded under both scenarios, the highly suitable area contracted significantly under SSP585 compared to SSP245. This suggests the importance of incorporating climate change considerations into P. chinensis management strategies to address potential challenges arising from future ecosystem dynamics.